The Effect of Family Psychoeducation on Anxiety, Support and Self Efficacy on the Family of Patients with Tuberculosis - Kamilah, Nadhifatul; Pratiwi, Ika Nur; Hidayati, Laily; Smith, Graeme Drummond (International Journal of Psychosocial Rehabilitation, 2020)
Tuberculosis (TB) has a significant effect on both the sufferers and their family. The family members have been known to develop psychological problems such as anxiety, feeling that there is a lack of support, and poor self-efficacy. To date, little is known about how best to deal with psychosocial morbidity. This study aims to analyze the effect of psychoeducation on the anxiety, support, and self-efficacy of the TB patients’ families. This was a quasi-experimental study with a pre-posttest design involving 28 participants for each of the control and intervention groups. The patients were selected using consecutive sampling based on their admission to the hospital in-patient wards. The intervention group received a 60-minute session on family psychoeducation comprised of an information session, discussion and a question and answer sub-session. The primary outcome measures were anxiety, family support and the self-efficacy of the family members. The data was retrieved using questionnaire and then analyzed using the Mann Whitney and Wilcoxon Signed Rank tests with a significance level α £ 0.05. Family psychoeducation significantly decreased anxiety (p = 0,000) and increased the family support (p= 0.001) and self-efficacy of the family members (p = 0,000). Family psychoeducation is an informational transfer motivator for patients. It was forms an adaptive coping mechanism so then any anxiety can be overcome. It affects the personal and interpersonal factors of the respondents’ related t forming self-efficacy. Family psychoeducation may have the positive benefit of solve family psychological problems, thus there is a need for support from internal and external resources.